2022
DOI: 10.1097/mph.0000000000002593
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Hepatoblastoma and Wilms Tumor Leading to Diagnosis of Beckwith-Wiedemann Syndrome

Abstract: Beckwith-Wiedemann syndrome (BWS) is an epigenetic overgrowth disorder and cancer predisposition syndrome caused by imprinting defects of chromosome 11p15.5-11p15.4. BWS should be considered in children with atypical presentations of embryonal tumors regardless of clinical phenotype. Risk of malignancy correlates with specific molecular subgroups of BWS making molecular subclassification important for appropriate cancer screening. We report the first case of concurrent embryonal tumors in a phenotypically norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…NR-interacting protein 3 (NRIP3) is a novel transcriptional coregulator of NR, which is located on chromosome 11p15.4, a fragile site associated with cancer. A recent study conducted by Wolfe et al ( 11 ) reported that defects of this region were related to embryonal tumors. However, the precise regulatory mechanisms and expression patterns of NRIP3 in CRC remain elusive.…”
Section: Introductionmentioning
confidence: 98%
“…NR-interacting protein 3 (NRIP3) is a novel transcriptional coregulator of NR, which is located on chromosome 11p15.4, a fragile site associated with cancer. A recent study conducted by Wolfe et al ( 11 ) reported that defects of this region were related to embryonal tumors. However, the precise regulatory mechanisms and expression patterns of NRIP3 in CRC remain elusive.…”
Section: Introductionmentioning
confidence: 98%
“…This assertion is rooted in well documented two-hit models, wherein the occurrence of genetic mutations in critical genes manifests as the cornerstone of tumorigenesis [12]. Resultant tumors predominantly manifest as blastoma types, encompassing pleuropulmonary blastomas, hepatoblastomas, and nephroblastomas (Wilms tumor) [13,14 ▪ ,15]. Furthermore, many of these syndromes are characterized by the presence of vascular malformations, hyperinsulinism, and developmental delays.…”
Section: Introductionmentioning
confidence: 99%